Late Miocene origin of an Ibero‐Maghrebian clade of ground beetles with multiple colonizations of the subterranean environment. (29th May 2014) - Faille, Arnaud; Andújar, Carmelo; Fadrique, Floren; Ribera, Ignacio; Rocha, Luiz
Abstract Aim To test different biogeographical scenarios for the evolution of the ground beetles of the Trechus fulvus group, a lineage with many narrowly distributed flightless subterranean species, highly suitable for tracing their biogeographical history. Location The Western Palaearctic, focusing on the Betic–Rifean area between south‐east Iberia and north Morocco. Methods We sequenced 3.3 kb of four mitochondrial and two nuclear genes of 30 individuals of 15 species of the T. fulvus group, plus 29 outgroups. We reconstructed their phylogeny and estimated divergence times using Bayesian probabilities and a priori evolutionary rates, and their ancestral distribution using maximum likelihood. Results The phylogenetic reconstruction uncovered multiple independent colonizations of the subterranean environment within the T. fulvus group, a scenario also supported by variation in troglomorphic characters. Most of the Moroccan and south‐east Iberian species form a clade with strong geographical structure, including the former genus Antoinella. The biogeographical model best fitting the current distribution and phylogeny of the group was a late Miocene palaeogeographical scenario with isolated populations on the Betic and Rifean areas and a south‐eastern Iberian origin of the north Moroccan species. The widespread T. fulvus was sister to a central Moroccan species, suggesting a second Iberian–North African vicariance event within the group. One of the species, T. lallemantii, expanded its range to the east (Algeria and Tunisia) and the north (extreme south of the Iberian Peninsula) during the Pleistocene. Main conclusions The T. fulvus group originated in the early Miocene, and the south‐eastern Iberian lineage in the Tortonian. The lineage dispersed to Morocco during the Messinian, diversifying in rapid succession in the Atlas and the Rif and colonizing the subterranean environment multiple times. The geography of the Betic–Rifean region at the end of the Miocene can still be traced from the distribution of the extant species of the group.